RESPON PERTUMBUHAN TANAMAN Desmodium heterophyllum WilldD.CDENGAN PEMBERIAN FUNGI MIKORIZA ARBUSKULAR (FMA) PADA TANAH LAHAN BEKAS TAMBANG BATU BARA SAWAH LUNTO - Yossi Eka Saputri; Zozy Aneloi Noli; Suwirmen Suwirmen (Biology Department, Mathematics and natural science, Tadulako University, 2016)
The study about the growth response of Desmodium heterophyllum plant by the treatnent with Arbuscular Mycorrizhal Fungy (AMF) on the soil of former coal aquarry in Sawah lunto, had been carnied out from Mayto July 2015 in the Nurseries and Reforaestation of Andalas University and continued at the Laboratory of Plant Physiology and Tissue Culture of Biology Department, the faculty of Mathematics and Natural Sciences, Andalas University, Padang. The research aimed to find out the best doses of AMFadministered the growth of D.heterophyllum growth on the soil of former coal quarry in Sawah lunto. The research used Completely Randomized Design (CRD), with five treatments and four replications. The treatments were without inoculation (control), inoculation with 5 g / plant, 10 g / plant, 15 g / plant, and 20 g / plant. The result showed that AMF inoculation in general gave significant effects for the plant height, the number of leaves, root plant weight and total dry weight, but did not effect on the increase of stem dry weight and leaves dry weight. The best doses for the growth of D.heterophyllumon the former coal quarry soil was at 5g/ plant doses. Keywords : Desmodium heterophyllum, AMF, Coal Mine Land.